Application of Human-Centered Design Principles in WebMed Application UI/UX Development - Sinlae, Fried; Alfauzi Hidayatullah, Dimas; Rizqi Sanjaya, Hafiyan; Situmorang, Lusiana (Siber Journal of Advanced Multidisciplinary, 2024)
This research explores the application of Human-Centered Design (HCD) principles in developing the user interface (UI) and user experience (UX) for the WebMed telemedicine application. The HCD method employed consists of three main stages: inspiration, ideation, and implementation. In the inspiration phase, data collection was conducted through observation and questionnaires to understand user needs. The ideation phase involved brainstorming and prototyping using Figma. The prototype included features such as a home page, list of doctors, list of medications, payment, and invoice. During the implementation phase, the prototype was tested by potential users. Test results showed general satisfaction with the UI/UX design, but also identified some areas requiring improvement, such as the home page appearance and menu icon design. This study demonstrates the effectiveness of the HCD approach in developing digital health applications that meet user needs, while emphasizing the importance of continuous iteration and testing in the UI/UX development process.